PENGARUH TIME PRESSURE, RISIKO AUDIT, TURNOVER INTENTION, PROSEDUR REVIEW DAN KONTROL KUALITAS TERHADAP PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT ( STUDI EMPIRIS PADA AUDITOR KANTOR AKUNTAN PUBLIK DI PEKANBARU, PADANG DAN MEDAN) - Handayani, Vina; ', Yusralaini; Natariasari, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine the effect of time pressure, audit risk, turnover intention, review procedure and quality control on premature signed off of audit procedure. This study was conducted at the public accounting firm in Pekanbaru, Padang and Medan. The population in this study were employed who worked in the public accounting firm in Pekanbaru, Padang and Medan (34 the public accounting firm). The sampling method used in this study is saturated sampling method. The respondent in this study is the senior auditor, junior auditor and supervisor. The sample used in this study were 102 respondents. The hypotheses then tested is multiple linear regression analysis by using SPSS version 21.0. The logistic regression show that time pressure, audit risk, turnover intention, review procedure and quality control have an effect on premature signed off of audit procedure. The magnitude of the effect (R2) t influence of time pressure, audit risk, turnover intention, review procedure and quality control on premature signed off of audit procedure was 74,5%. While the remaining 25,5% is influenced by other independent variabel that are not observed in this study.Keyword : time, turnover, procedur, quality, and audit